2019
DOI: 10.1093/jpe/rtz027
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation and seasonality affect grazing impacts on herbage nutritive values in alpine meadows on the Qinghai-Tibet Plateau

Abstract: Aims Grasslands used for animal husbandry are chosen depending on the nutritive values of dominant herbage species. However, the influence of grazing in combination with precipitation and growing season on the nutritive values of dominant species has not been explicated. Methods To unveil the influence of the different grazing intensities on the nutritional values, an ecological study was formulated, namely fencing (G0), ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…The content of CP, ADF (16.26%-55.39%), NDF, EE (2.48%-4.38%), Ash (7.89%-21.95%) and WSC (3.08%-6.76%) in this study were equivalent to the results (CP: 2.71%-19.21%; ADF: 9.06%-48.30%; NDF: 12.16%-76.23%; EE: 0.64%-10.90%; Ash: 3.49%-12.47%; WSC: 1.24%-17.27%) observed in alpine meadows on the Tibetan Plateau by previous studies (Xu et al, 2002;Shi et al, 2013;Sun et al, 2015;Zhang et al, 2015b;Fan et al, 2017;Li and Liu, 2017;Zhang et al, 2017;Li et al, 2018). Increased water availability may have increased the content of CP in this study, which was in line with the results observed in the steppes of Inner Mongolia Autonomous Region, China (Schönbach et al, 2012;Ren et al, 2016a), a C4 tropical grass in Brazil (Habermann et al, 2019), mountain side grasslands in North-West Greece (Roukos et al, 2011) and alpine meadows on the Tibetan Plateau (Yao et al, 2019). This finding may be related to several mechanisms.…”
Section: Discussionsupporting
confidence: 86%
“…The content of CP, ADF (16.26%-55.39%), NDF, EE (2.48%-4.38%), Ash (7.89%-21.95%) and WSC (3.08%-6.76%) in this study were equivalent to the results (CP: 2.71%-19.21%; ADF: 9.06%-48.30%; NDF: 12.16%-76.23%; EE: 0.64%-10.90%; Ash: 3.49%-12.47%; WSC: 1.24%-17.27%) observed in alpine meadows on the Tibetan Plateau by previous studies (Xu et al, 2002;Shi et al, 2013;Sun et al, 2015;Zhang et al, 2015b;Fan et al, 2017;Li and Liu, 2017;Zhang et al, 2017;Li et al, 2018). Increased water availability may have increased the content of CP in this study, which was in line with the results observed in the steppes of Inner Mongolia Autonomous Region, China (Schönbach et al, 2012;Ren et al, 2016a), a C4 tropical grass in Brazil (Habermann et al, 2019), mountain side grasslands in North-West Greece (Roukos et al, 2011) and alpine meadows on the Tibetan Plateau (Yao et al, 2019). This finding may be related to several mechanisms.…”
Section: Discussionsupporting
confidence: 86%
“…Differences in growth phenology relative to the timing of drought may explain this disparity as Biserrula, an annual species, reached peak growth in early spring when the drought treatment was first implemented for this species, suggesting that residual soil water from winter may have been sufficient to support strong early growth despite the spring drought (Fay et al, 2000;Hofer et al, 2017). These differences in legume response, along with the large effects of winter/spring drought on cool season productivity of our tropical grasses-effects that persisted during the more productive, warm season for one (Themeda) of the three C4 species -provide support for the importance of drought timing in relation to species growth phenology (Wilcox et al, 2017;Yao et al, 2019) rather than functional group classifications.…”
Section: Productivity Responses To Winter/spring Droughtmentioning
confidence: 86%
“…However, unlike Medicago, a perennial whose swards develop over multiple years (Li et al, 2012), Biserrula is an annual species, regenerating from seed early in spring each year. These life history differences that influence growth seasonality along with the significant effect of winter/spring drought on productivity of the tropical (C4) grasses, highlight the importance of drought timing in relation to species' growth phenology (Wilcox et al, 2017;Yao et al, 2019), which is at least partially reflected in their functional group classifications.…”
Section: Productivity Responses To Winter/spring Droughtmentioning
confidence: 99%
“…1F), suggesting that by the criteria provided by Koerselman and Meuleman (1996), P was limiting to the growth of P. fruticose. Soil P de ciency is common across China (Han et al, 2005;Zhao et al, 2016), including the whole QTP (Niu et al, 2016) and the Qilian Mountains Xu et al, 2018aXu et al, , 2019Cao et al, 2020). However, Reich and Oleksyn (2004) concluded that plant growth in high elevations was more limited by N. This suggests that limitation of nutrient elements for plants is dependent on region.…”
Section: Limiting Nutrients For P Fruticosa Across Elevationsmentioning
confidence: 99%
“…Similarly, factors such as transportation and industrial pollution in uence its leaf morphology and the elemental composition of its organs (Lugovskaya et al, 2018). Likewise, salinity (NaCl and Na 2 SO 4 ) in uence its leaves' physiological and biochemical characteristics (Liu et al, 2013), while grazing in uences its nutritive value (Yao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%